1940
DOI: 10.1515/bchm2.1940.264.3-4.91
|View full text |Cite
|
Sign up to set email alerts
|

Über die optische Aktivität der durch biochemische Synthese entstandenen Acetoine

Abstract: In einer jüngst erschienenen Arbeit 1 ) aus dem hiesigen Institut wurden Versuche über Acetoinbildung durch Erbsenmehl veröffentlicht, welche Dirscherls 2 ' 3 ) Auffassung beim Problem der "Carboligase" unterstützten. Die Frage, ob dabei optisch aktives Acetoin entsteht, wurde dort nicht berührt. Die optische Aktivität des enzymatisch gebildeten Acetoins wurde von mehreren Seiten als ein Beweis für die Existenz einer selbständigen "Carboligase" betrachtet, nach Dirscherl und Schöllig 4 ) (vgl. dort einschlägig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1945
1945
2011
2011

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The acetoin produced by PDC from pyruvate had [a]27D = -45°( ±1°), hence consisted of 77 (-) and 23% (+) enantiomer. These numbers are based on the [a]27D = -84°( ±2°) obtained for (-)-acetoin isolated from a number of bacteria and tissues (Tanko et al, 1940; Berl & Bueding, 1951; Juni, 1951b) and confirmed by Singer & Pensky (1952a). No evidence for racemization was obtained under the reaction and purification conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The acetoin produced by PDC from pyruvate had [a]27D = -45°( ±1°), hence consisted of 77 (-) and 23% (+) enantiomer. These numbers are based on the [a]27D = -84°( ±2°) obtained for (-)-acetoin isolated from a number of bacteria and tissues (Tanko et al, 1940; Berl & Bueding, 1951; Juni, 1951b) and confirmed by Singer & Pensky (1952a). No evidence for racemization was obtained under the reaction and purification conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The nearly quantitative formation of acetoin in brain homogenates from acetaldehyde in the presence of pyruvate has been demonstrated (186), while smaller amounts of acetoin were formed from pyruvate or acetaldehyde alone. Tank6 and coworkers (193), although demonstrating principally the formation of 1-acetoin in animal tissue preparations, suspect the presence of admixture with the unnatural isomer. Tank6 and coworkers (193), although demonstrating principally the formation of 1-acetoin in animal tissue preparations, suspect the presence of admixture with the unnatural isomer.…”
Section: Deeurbozylationmentioning
confidence: 99%
“…CHsCOCOOH -CHjCHO + CO, CHaCHO + CHICOCOOH -CHICOCHOHCH, + COe Acetaldehyde has been "trapped" by aldehyde fixatives in autolyzing tissues (87,158,196,217), and acetoin formation from pyruvate has been demonstrated in minced heart muscle (76), skeletal muscle, liver and kidney (193). The nearly quantitative formation of acetoin in brain homogenates from acetaldehyde in the presence of pyruvate has been demonstrated (186), while smaller amounts of acetoin were formed from pyruvate or acetaldehyde alone.…”
Section: Deeurbozylationmentioning
confidence: 99%